A Comparison of Tensile and Flexural Properties of Jute Mat Epoxy-Based Composites Treated with Different Alkaline Solutions - Aseel M. Abdullah (Tikrit Journal of Engineering Sciences)
Each year has seen the high intricacy utilized of natural fiber/polymer-based composites in most engineering sectors due to the good mechanical performance and low cost. In this work, three layers of jute fiber mats were examined as reinforcement for thermosetting-based composite materials prepared by the hand lay-up process. An alkali chemical treatment with different types of solutions (NaOH, KOH, and LiOH) and concentrations (2%, 4%, and 6% wt) was used to treat jute fibers with the point of enhancing the ability of adhesion between the surface of the jute mat and epoxy resin. Various mechanical tests like tensile and flexural have been studied by comparing the results and performance of different types of alkali treatment. The experimental results indicated that alkali treatments were more efficient for flexural behavior than tensile. The highest tensile and bending strengths were shown in the concentration of 6% wt NaOH 31% and 90%, respectively, better than the untreated composite.